ANALISIS PENGARUH TEORI KOGNITIF JEAN PIAGET TERHADAP PERKEMBANGAN MORAL SISWA SEKOLAH DASAR MELALUI PEMBELAJARAN IPS - Dwi Wijayanti (Universitas Sarjanawiyata Tamansiswa, 2015)
Abstract:Jean Piaget is known as the founder of constructivist learning. The theory regardes basically each studenthasknowledge before they have been treated in learning process. Cognitive development is also covering theory of moral logical development. A social study learning is learning closely related to value and morality, a social study learning will tend to social cognition so influents students’ morality. In fact, social study learning is still experiencing some problems. Therefore, value and moralityinternalizationto social study learning needs to be prepared and planned continuously by pressing to each different level. The higher cognitive level is the more mature comprehensive element and responsibility. Due to, the attitude and their action will always be based by responsibility to their selves and environment.